Perancangan Sistem Informasi Pendaftaran Kerja Praktik di PTTelkom Akses Medan Berbasis Mobile - Samsudin, Samsudin; Pratiwi, Yulisa Nanda (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Samsudin1), 1Sistem Informasi, Sains dan teknologi, Universitas Islam Negeri Sumatera utara email: samsudin@uinsu.ac.id, yulisananda7@gmail.com ABSTRACT Telkom Akses Medan is one of the subsidiaries of PT. Telekomunikasi Indonesia Tbk which is engaged in the business of providing construction services and managing network infrastructure. Although this agency is engaged in information technology and networks. But not all activities involve technology. For example, in the registration of practical work at PT. Telkom Akses Medan does not yet have an information system that can support and assist in the registration process and acceptance of practical work from registrants. So that the registrants register manually, namely by coming directly to PT. Telkom Access Medan and brings an application letter and certain conditions needed to apply for practical work registration. With some of these processes, there are several obstacles such as, having to come directly to the company and practical work registrants having to wait for a reply letter that is uncertain when it will come out. Resulting in a series of practical work registration processes being less effective and efficient. With this complicated practical work registration application process, it encouraged us to design an information system for practical work registration at PT. Telkom Access Medan is mobile-based. As a solution to this problem is described with UML (Unified Modeliling Language). In this design, the method used is the waterfall development metedo. Keywords: Information System, UML, Registration, Practical Work